Muscle strengthening in individuals with Amyotrophic Lateral Sclerosis: a systematic review with meta-analyses - Aline Alves de Souza; Stephano Tomaz da Silva; Amanda Mayra Pereira Régis; Diogo Neres Aires; Karen de Medeiros Pondofe; Luciana Protásio de Melo; Ricardo Alexsandro de Medeiros Valentim; Ana Raquel Rodrigues Lindquist; Lorenna Raquel Dantas de Macedo; Tatiana Souza Ribeiro (PLoS ONE, 2025)
Despite the observed benefits of properly prescribed exercises for people with Amyotrophic Lateral Sclerosis (ALS), the scarcity of studies and lack of consensus on the effects of muscle-strengthening exercises on this population has a negative impact on their rehabilitation. This study aimed to evaluate the effects of muscle-strengthening interventions in individuals with ALS. This systematic review of intervention studies included clinical trials that performed non-respiratory muscle strengthening in people with ALS compared to non-strengthening interventions, usual care, or placebo. Such studies were obtained from the MEDLINE, EMBASE, Cochrane Library, SPORTDiscus, and Physiotherapy Evidence Database databases, with no language or publication date restrictions. The outcomes considered were peripheral muscle strength, functionality, fatigue, and adverse events. The Physiotherapy Evidence Database scale was used to analyze the risk of bias, while the Grading of Recommendations Assessment, Development and Evaluation system was used to evaluate the quality of the evidence. Searches were conducted in October 2023 and eight studies were included, totaling 296 individuals. Seven of the eight studies showed superiority of the experimental intervention over the control, but this was not supported in the meta-analyses. Small sample size and high heterogeneity in the primary studies contributed significantly to the low quality of the evidence. There was no evidence of the superiority of interventions for muscle strengthening compared to interventions not aimed at strengthening, usual care, or placebo in terms of the outcomes analyzed immediately after the intervention. The quality of the evidence ranged from low to very low. Five of the studies evaluated adverse events, without reporting serious events. Interventions for muscle strengthening did not prove to be more effective when compared to the control group in the short term nor seem to produce serious adverse events. The low quality of the evidence indicates the need for studies with greater methodological rigor in this population, to more assertively assess the impacts of this intervention over the short, medium, and long term.